Effect of apple fibre on textural and relaxation properties of wheat chips dough - Karaman, S.; Yilmaz, M. T.; Toker, O. S.; Yuksel, F.; Kayacier, A.; Dogan, M. (WAGENINGEN ACADEMIC PUBLISHERS, 2016)
In this study, the effect of apple fibre with different levels of fibres (5, 10, 15 and 20%) was investigated on viscoelastic nature and the textural properties of wheat chips dough using stress relaxation test and texture profile analysis. Apple fibre addition changed the stress relaxation properties of wheat dough, depending on fibre concentration. Increase in the fibre concentration increased resistance of the dough samples to the deformation by increasing their elasticity. Hardness and gumminess values increased while springiness, cohesiveness and resilience values decreased as apple fibre level increased. Significant correlations were found between stress relaxation and texture profile analysis parameters. In order to describe the effect of apple fibre on the viscoelastic properties of wheat dough, generalised Maxwell, Nussinovitch and Peleg models were fitted to experimental stress relaxation data. All three models were found to be efficient in describing the stress-relaxation behaviour of wheat dough; but, the Maxwell model was the most effective. In addition, power-law and exponential functions were successfully used to describe the effect of apple fibre concentration on the constants related with stress relaxation data and textural parameters.
Keywords: fibre; dough; stress relaxation; texture; wheat chips; viscoelastic; STRESS-RELAXATION; VISCOELASTIC PROPERTIES; BREAD QUALITY; RHEOLOGICAL PROPERTIES; DIETARY FIBER; PHYSICOCHEMICAL PROPERTIES; FLOUR ADDITION; MODEL SYSTEM; BARLEY; FRUIT; Food Science & Technology